The impacts of the trails on property values surrounding Jejudo in Korea: using quantile regressions. (1st September 2016) - Jung, Su Yeon
Abstract: The purpose of this study is to quantitatively analyze the effect of Jeju Olle Trails on nearby land prices. Land sale prices are designated as the dependent variable and zoning type and land category, shape of the land, and the width of bordering roads as independent variables. Land price data for actual sales for seven areas surrounding Olle Trails were examined with a geographic information system program to determine the exact distance of land parcels from nearby trekking courses. A quantile regression model is used to estimate the effect of trail proximity to nearby land prices. Through this quantile regression model, the difference in the effects of trail proximity between low-priced and high-priced land is captured. This study shows no significance for the variable up to quantile 0.6; however, the variable becomes significant from the 0.7 quantile and up. This suggests that plots in the top 30% of land prices are affected by the presence of trails, but the plots in the bottom 70% are not affected by this variable. For every 100 m distance from an Olle Trail, land price falls by 0.054%.